Asymmetrical color filling-in from the nasal to the temporal side of the blind spot - Li, Hui; Luo, Junxiang; Lu, Yiliang; Kan, Janis; Spillmann, Lothar; Wang, Wei (Frontiers in Human Neuroscience, 2014)
The physiological blind spot, corresponding to the optic disk in the retina, is a relatively large (6x8 deg) area in the visual field that receives no retinal input. However, we rarely notice the existence of it in daily life. This is because the blind spot fills in with the brightness, color, texture, and motion of the surround. The study of filling-in enables us to better understand the creative nature of the visual system, which generates perceptual information where there is none. Is there any retinotopic rule in the color filling-in of the blind spot? To find out, we used mono-colored and bi-colored annuli hugging the boundary of the blind spot. We found that mono-colored annuli filled in the blind spot uniformly. By contrast, bi-colored annuli, where one half had a given color, while the other half had a different one, filled in the blind spot asymmetrically. Specifically, the color surrounding the nasal half typically filled in about 75% of the blind spot area, whereas the color surrounding the temporal half filled in only about 25%. This asymmetry was dependent on the relative size of the half rings, but not the two colors used, and was absent when the bi-colored annulus was rotated by 90 deg. Here, the two colors on the upper and lower sides of the blind spot filled in the enclosed area equally. These results suggest that the strength of filling-in decreases with distance from the fovea consistent with the decrease of the cortical magnification factor.